Associations between perceived overload and quality of care in dementia family caregivers in China: mediating role of familism and social support - Zou, Ni; Cai, Chan; Zhou, Xinyu; Chen, Shunian; Shi, Jiabi; Shi, Chongqing (Frontiers in Public Health, 2024)
BackgroundThe quality of care (QoC) of people with dementia is an issue of widespread concern in public health. While perceived overload of family caregivers is thought to negatively affect QoC, the underlying mechanisms of this relationship are not well understood. This study aimed to examine the multiple mediating roles of familism and social support in the relationship between perceived overload and QoC among people with dementia (PwD) within the contemporary Chinese context.MethodsA cross-sectional study was conducted between February 2023 and October 2023 in three hospitals located in three cities in Hubei Province, China. A total of 213 PwD and their family caregivers were recruited. Participants completed a general demographic questionnaire, the Chinese version of the Overload Scale, the Social Support Rating Scale (SSRS), the Familism Scale (FS), and the Exemplary Care Scale (ECS). Data were analyzed using SPSS 26.0 and the PROCESS macro.ResultsPerceived overload among family caregivers was directly related to QoC. Multiple mediation analysis revealed that the relationship between perceived overload and QoC was mediated by familism (effect: −0.111, 95% CI [−0.221, −0.034]) and social support (effect: −0.078, 95% CI [−0.163, −0.007]) both independently and serially (effect: −0.024, 95% CI [−0.054, −0.004]).ConclusionFamilism and social support serve as multiple mediators in the relationship between perceived overload and QoC. This underscores the importance of incorporating familism and social support into intervention strategies aimed at enhancing QoC.